Gel battery and preparation method thereof
By forming the structure of the core, SEI film coating and gel polymer coating on the negative electrode active material, the shortcomings of existing gel batteries in terms of rate performance and high-temperature storage performance are solved, and higher battery performance is achieved.
Patent Information
- Application Number
- CN202411454836.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-03-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing gel polymer electrolyte power batteries have shortcomings in terms of rate performance and high-temperature storage performance, especially during the circulation of silicon-based negative electrode materials, volume changes lead to the growth and rupture of the solid electrolyte layer, causing rapid capacity decline.
The structure of a core, a first cladding layer and a second cladding layer is formed on the negative electrode active material, wherein the first cladding layer consists of a SEI film generated by the reaction of the electrolyte with the negative electrode active material, the second cladding layer consists of a gel polymer including a fluorine-containing monomer, and the thickness of the cladding layer is controlled to be between 0.3-0.5 μm.
Effectively reduce the interface impedance, stabilize the SEI film, suppress the side reaction between the electrolyte and the active material under high-temperature storage conditions, improve the problem of continuous decomposition of electrolytes on the electrode surface, and reduce the loss of irreversible capacity, thereby improving the rate performance and high-temperature storage performance of gel batteries.
Smart Images

Figure CN119601758A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion batteries and relates to a preparation method of a gel battery, in particular to a preparation method of a gel battery and an application thereof. Background Art
[0002] With the development of technology and the continuous growth of market demand, batteries are developing with high energy density, and need to match positive and negative electrode materials with higher energy density. Layered ternary positive electrode materials and silicon-based negative electrode materials are widely used due to their high energy density. However, the silicon-based negative electrode will undergo huge volume changes during the cycle, causing the solid electrolyte layer (SEI) to continue to grow and rupture, continuously consuming the electrolyte, and causing rapid capacity decline.
[0003] In-situ gel electrolyte can provide good mechanical strength, help maintain the stability of the electrode structure, and is easy to operate, and has become an effective way to inhibit the expansion of silicon negative electrodes. However, most existing gel polymer electrolyte power batteries have problems with poor rate performance and high-temperature storage performance.
[0004] Therefore, it is necessary to further improve the rate performance and high temperature storage performance of gel batteries. Summary of the invention
[0005] In view of the above defects, the present invention provides a gel battery having high rate performance and high temperature storage performance.
[0006] The present invention also provides a method for preparing the gel battery. The gel battery prepared by the method has high rate performance and high-temperature storage performance.
[0007] The present invention provides a gel battery, which comprises a negative electrode sheet and a gel electrolyte;
[0008] The gel electrolyte comprises an electrolyte and a gel polymer, and the gel polymer is obtained by polymerizing a raw material system comprising a fluorine-containing monomer;
[0009] The negative electrode sheet comprises a negative electrode active material, wherein the negative electrode active material comprises a core and a coating layer, wherein the coating layer comprises a first coating layer and a second coating layer, wherein the first coating layer is located on at least a portion of an outer surface of the core, and the second coating layer is located on a surface of the first coating layer away from the core, or the second coating layer is located on a surface of the first coating layer away from the core and on a surface of the core;
[0010] The core includes a negative electrode material that can be used for active ion embedding and extraction, the first coating layer includes a SEI film, and the second coating layer includes the gel polymer;
[0011] The coating layer has a thickness of 0.3-0.5 μm.
[0012] Furthermore, the fluorine-containing monomer includes at least one of trifluoroethyl methacrylate, 1,1,1,3,3,3-hexafluoroisopropyl methacrylate, trifluoroethyl acrylate, hexafluorobutyl acrylate, hexafluorobutyl methacrylate, and octafluoropentyl methacrylate.
[0013] Further, the electrolyte includes an additive;
[0014] The additive includes fluoroethylene carbonate and / or vinylene carbonate.
[0015] Furthermore, the mass percentage of the additive in the electrolyte is 5-12wt%.
[0016] The present invention also provides a method for preparing the above-mentioned gel battery, comprising the following steps:
[0017] 1) injecting a precursor solution including an electrolyte and a fluorine-containing monomer into a battery to obtain a first battery;
[0018] 2) Cycling the first battery 1-2 times according to the following charge and discharge mechanism to obtain a second battery; the charge and discharge mechanism includes: charging at a constant current and constant voltage of 0.08-0.12C to a battery working cut-off voltage at a pressure of 0.1-1.0MPa and a temperature not higher than 25°C, with a cut-off current of 0.05C, standing still, discharging at a constant current of 0.08-0.12C to a battery working cut-off voltage, and standing still;
[0019] 3) reacting the second battery at a pressure of 0.1-0.5 MPa and a temperature of 55-70° C. for a reaction time of not less than 24 hours to obtain a gel battery.
[0020] Furthermore, the mass percentage of the fluorine-containing monomer in the precursor solution is 6.5-19.0 wt %.
[0021] Furthermore, the precursor solution also includes a cross-linking agent;
[0022] The crosslinking agent includes at least one of pentaerythritol tetraacrylate, di(trimethylolpropane) tetraacrylate, trimethylolpropane triacrylate, and trimethylolpropane trimethacrylate;
[0023] And / or, the precursor solution further comprises an initiator;
[0024] The initiator includes azobisisobutyronitrile and / or azobisisoheptanenitrile.
[0025] Furthermore, the mass percentage of the cross-linking agent in the precursor solution is 0.8-2.0wt%.
[0026] Furthermore, the mass percentage of the initiator in the precursor solution is 0.01-0.05wt%.
[0027] Furthermore, the precursor solution includes, by weight percentage, 8-17 wt % of a fluorine-containing monomer, 0.8-1.5 wt % of a cross-linking agent, 0.01-0.05 wt % of an initiator, and the remainder being an electrolyte.
[0028] The present invention makes the negative electrode active material include a core and a first coating layer and a second coating layer, wherein the first coating layer includes an SEI film (i.e., a solid electrolyte film, generated by the reaction of an electrolyte and a negative electrode active material), which is located on at least part of the surface of the core, and can effectively reduce the interface impedance; the second coating layer includes a gel polymer, which is located on the surface of the first coating layer or the surface of the core and the first coating layer. Since the gel polymer is obtained by polymerization of a raw material system including a fluorine-containing monomer, it can play a role in stabilizing the SEI film, and at the same time, it can also effectively inhibit the continuous side reaction of the electrolyte and the active material under high-temperature storage conditions, prevent the continuous growth of the SEI film, improve the problem of continuous decomposition of the electrolyte on the electrode surface, and reduce the loss of irreversible capacity. Thus, the rate performance and high-temperature storage performance of the gel battery can be comprehensively improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 is a schematic diagram of the structure of the negative electrode active material particles of the present invention;
[0030] Figure 2 The discharge capacity variation diagram of the gel battery in Example 1 of the present invention and Comparative Example 1 at different rates;
[0031] Figure 3 The discharge capacity variation diagram of the gel battery in Example 2 of the present invention and Comparative Example 2 at different rates;
[0032] Figure 4 This is an EIS test diagram of the gel battery in Example 1 of the present invention before and after high temperature storage;
[0033] Figure 5 This is an EIS test diagram of the gel battery in Example 2 of the present invention before and after high temperature storage;
[0034] Figure 6 This is an EIS test diagram of the gel battery in Comparative Example 1 of the present invention before and after high-temperature storage;
[0035] Figure 7 This is an EIS test diagram of the gel battery in Comparative Example 2 of the present invention before and after high temperature storage;
[0036] Figure 8is a cross-sectional SEM image of the negative electrode active material in the gel battery of Example 2 of the present invention at 6.00K;
[0037] Fig. 9 is a cross-sectional SEM image of the negative electrode active material in the gel battery of Example 2 of the present invention at 10.0K;
[0038] Fig.10 This is a cross-sectional SEM image of the negative electrode active material in the gel battery in Comparative Example 2 of the present invention at 6.00K;
[0039] Fig.11 This is a cross-sectional SEM image of the negative electrode active material in the gel battery in Comparative Example 2 of the present invention at 10.0K.
[0040] 1-first coating layer;
[0041] 2- second coating layer;
[0042] 3- Kernel. DETAILED DESCRIPTION
[0043] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0044] A first aspect of the present invention provides a gel battery, the gel battery comprising a negative electrode sheet and a gel electrolyte;
[0045] The gel electrolyte includes an electrolyte and a gel polymer, and the gel polymer is obtained by polymerizing a raw material system including a fluorine-containing monomer;
[0046] The negative electrode sheet includes a negative electrode active material, the negative electrode active material includes a core and a coating layer, the coating layer includes a first coating layer and a second coating layer, the first coating layer is located on at least a portion of the outer surface of the core, the second coating layer is located on a surface of the first coating layer away from the core, or the second coating layer is located on a surface of the first coating layer away from the core and on a surface of the core;
[0047] The core includes a negative electrode material for active ion embedding and extraction, the first coating layer includes a SEI film formed by reaction with an electrolyte, and the second coating layer includes a gel polymer;
[0048] The thickness of the coating layer is 0.3-0.5 μm.
[0049] Exemplarily, the coating layer has a thickness of 0.3 μm, 0.35 μm, 0.4 μm, 0.45 μm or 0.5 μm.
[0050] Figure 1 is a schematic diagram of the structure of the negative electrode active material particles, such as Figure 1 As shown, the negative electrode active material includes a core 3, a first coating layer 1 and a second coating layer 2, wherein the first coating layer 1 is located on at least a portion of the outer surface of the core 3, the second coating layer 2 is located on the outer surface of the first coating layer 1, or the second coating layer 2 is located on the outer surface of the first coating layer 1 and the outer surface of the core 3.
[0051] The "fluorine-containing monomer" in the present invention refers to a monomer compound containing fluorine atoms in its molecular structure.
[0052] The present invention does not specifically limit the type and source of the fluorine-containing monomer, and any commercially available product or a product prepared by a conventional preparation method well known to those skilled in the art may be used.
[0053] The present invention does not specifically limit the type and source of the negative electrode material, and a silicon-based negative electrode material is preferably used.
[0054] It can be understood that the gel battery also includes a positive electrode sheet and a separator. The positive electrode sheet includes a positive electrode current collector and a positive electrode active layer. The positive electrode active layer includes a positive electrode active material.
[0055] The present invention does not specifically limit the positive electrode active material, positive electrode current collector and separator, which are all conventionally selected in the art.
[0056] Since the negative electrode active material will undergo intercalation or alloying of lithium during the charge and discharge process, there will be a significant volume expansion, especially the volume change of silicon-based negative electrode active materials is more significant. In this process, the negative electrode active material will have a continuous side reaction with the electrolyte, consuming the electrolyte, and the SEI film will continue to grow and rupture, resulting in a sharp decline in battery capacity. Although gel electrolyte can alleviate this side reaction to a certain extent, it will cause the interface impedance to rise, affecting the battery's rate performance and high-temperature storage performance.
[0057] The present invention makes the negative electrode active material include a core and a first coating layer and a second coating layer, wherein the first coating layer is located on at least part of the outer surface of the core, and the coating layer includes an SEI film, that is, a solid electrolyte film generated by the reaction of the negative electrode active material and the electrolyte, which is beneficial to reduce the interface impedance and improve the ionic conductivity and electronic conductivity of the material; at the same time, a second coating layer is arranged on the outer surface of the first coating layer or the outer surface of the first coating layer and the core, and the coating layer includes a gel polymer formed by the polymerization of fluorine-containing monomers, which can effectively isolate the negative electrode active material from the electrolyte, prevent the continuous growth and rupture of the SEI film under high-temperature storage conditions, and reduce the consumption of the electrolyte; on the other hand, the gel polymer formed by the polymerization of fluorine-containing monomers can also effectively improve the stability of the SEI film. Therefore, the rate performance and high-temperature storage performance of the gel battery can be comprehensively improved.
[0058] In a specific embodiment, the fluorine-containing monomer includes at least one of trifluoroethyl methacrylate, 1,1,1,3,3,3-hexafluoroisopropyl methacrylate, trifluoroethyl acrylate, hexafluorobutyl acrylate, hexafluorobutyl methacrylate and octafluoropentyl methacrylate. When the aforementioned compound is a mixture of multiple specific compounds, the present invention does not impose too many restrictions on the ratio between the specific compounds.
[0059] In a specific embodiment, the electrolyte includes an additive; the additive includes fluoroethylene carbonate and / or vinylene carbonate. When the electrolyte includes the above-mentioned additive, a more stable, dense and uniform SEI film can be formed, which stabilizes the electrolyte and electrolytic interface, further reduces the interface impedance, and can further alleviate the problem of continuous decomposition of the electrolyte on the electrode surface, so that the battery has higher rate performance and high temperature storage performance.
[0060] When the additive is a mixture of multiple specific compounds, the present invention does not impose too many restrictions on the ratio between the specific compounds.
[0061] In a specific embodiment, the mass percentage of the additive in the electrolyte is 5-12wt%. For example, the mass percentage is 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, 11wt% or 12wt%. Within this range, it helps to further improve the rate performance and high temperature storage performance of the battery.
[0062] The second aspect of the present invention provides a method for preparing the gel battery of the first aspect, comprising the following steps:
[0063] 1) injecting a precursor solution including an electrolyte and a fluorine-containing monomer into a battery to obtain a first battery;
[0064] 2) Cycling the first battery 1-2 times according to the following charge and discharge mechanism to obtain a second battery; the charge and discharge mechanism includes: charging at a constant current and constant voltage of 0.08-0.12C to a battery working cut-off voltage at a pressure of 0.1-1.0MPa and a temperature not higher than 25°C, with a cut-off current of 0.05C, standing still, discharging at a constant current of 0.08-0.12C to a battery working cut-off voltage, and standing still;
[0065] 3) reacting the second battery at a pressure of 0.1-0.5 MPa and a temperature of 55-70° C. for a reaction time of not less than 24 hours to obtain a gel battery.
[0066] Specifically, in step 1), the electrolyte and the precursor solution including the fluorine-containing monomer are uniformly mixed and then injected into the baked lithium-ion battery. After the injection is completed, the mixture is allowed to stand at room temperature to obtain a first battery.
[0067] The present invention does not impose any specific limitation on the specific composition of the electrolyte, which can be selected conventionally in the art.
[0068] The present invention does not specifically limit the standing time, for example, the standing time is 8-24 hours.
[0069] In step 2), a battery clamp is used to charge the first battery at a pressure of 0.1-1.0MPa and a temperature not higher than 25°C at a constant current and constant voltage of 0.08-0.12C to the battery working cut-off voltage, and the cut-off current is 0.05C. After standing, the battery is discharged at a constant current of 0.08-0.12C to the battery working cut-off voltage, and then standing; the second battery is obtained after 1-2 times according to the above-mentioned charge and discharge mechanism. In step 3), the second battery is subjected to a curing reaction at a pressure of 0.1-0.5MPa and a temperature of 55-70°C, and the reaction time is not less than 24h. After the reaction is completed, the battery is allowed to stand and the capacity is divided to obtain a gel battery.
[0070] The present invention does not specifically limit the standing time. For example, the standing time is 8-16 hours.
[0071] The preparation method of the gel battery in the present invention uses a special fluorine-containing monomer to perform activation treatment and curing treatment on the lithium-ion battery injected with electrolyte and precursor solution at the same time. Specifically, it is first cycled twice under a specific charge and discharge mechanism, and then reacted for a certain period of time under a specific pressure and temperature. The prepared gel battery has high rate performance and high-temperature storage performance. Based on this phenomenon, the inventor analyzed and believed that the reason may be: by first activating the lithium-ion battery after injection, a stable, dense and uniform SEI film (i.e., the first coating layer) can be formed on the surface of the negative electrode active material in advance under a specific charge and discharge mechanism, effectively reducing the interface impedance. Then, the reaction is carried out for a certain period of time at a specific pressure and reaction temperature, and a curing treatment is performed to form a gel polymer (i.e., the second coating layer) around the negative electrode active material coated with the SEI film, which can effectively prevent the side reaction of the electrolyte and the active material under high-temperature storage conditions, improve the problem of continuous decomposition of the electrolyte on the electrode surface, and reduce the loss of irreversible capacity; at the same time, by controlling the thickness of the coating layer to 0.3-0.5μm, the interface impedance can be further reduced and the occurrence of side reactions can be reduced, thereby comprehensively improving the rate performance and high-temperature storage performance of the battery. When the charging current is too small, the activation time will be too long and the monomer will partially polymerize. When the charging current is too large, a SEI film with more inorganic lithium salt components will be generated accordingly, which will cause the SEI film structure to be loose, not dense enough and thicker. When the pressure is too high, the electrolyte will be squeezed to the edge of the battery cell, and when the pressure is too small, it will cause the electrolyte to be unevenly infiltrated. Therefore, only under the aforementioned charging and discharging mechanism and reaction conditions can the rate performance and high-temperature storage performance of the battery be effectively improved.
[0072] In a specific embodiment, the mass percentage of the fluorine-containing monomer in the precursor solution is 6.5-19.0wt%. For example, the mass percentage is 6.5wt%, 8.0wt%, 10.0wt%, 12.0wt%, 14.0wt%, 16.0wt%, 18.0wt% or 19.0wt%. Within this range, not only can the prepared gel electrolyte have a higher ionic conductivity, improve the diffusion capacity of lithium ions, reduce the internal resistance of the battery, and improve the charge and discharge capacity of the battery, but also the mechanical strength of the gel electrolyte can be effectively improved, the volume expansion of the negative electrode material during the cycle process can be suppressed, and the stability of the electrode structure can be improved, so that the gel battery has higher rate performance and cycle performance.
[0073] In a specific embodiment, the precursor solution further comprises a crosslinking agent; the crosslinking agent comprises at least one of pentaerythritol tetraacrylate, di(trimethylolpropane) tetraacrylate, trimethylolpropane triacrylate, and trimethylolpropane trimethacrylate;
[0074] In a specific embodiment, the precursor solution further includes an initiator; the initiator includes azobisisobutyronitrile and / or azobisisoheptanenitrile.
[0075] When the aforementioned two types of compounds are mixtures of multiple specific compounds, the present invention does not impose too many restrictions on the ratios between the specific compounds.
[0076] In a specific embodiment, the mass percentage of the crosslinking agent in the precursor solution is 0.8-2.0wt%. For example, the mass percentage is 0.8wt%, 1.0wt%, 1.2wt%, 1.4wt%, 1.6wt%, 1.8wt% or 2.0wt%. Within this range, the fluorine-containing monomer can be better crosslinked to avoid excessive crosslinking leading to a decrease in ionic conductivity, so that the prepared gel electrolyte has a higher ionic conductivity, further improving the rate performance of the gel battery.
[0077] In a specific embodiment, the mass percentage of the initiator in the precursor solution is 0.01-0.05wt%. For example, the mass percentage is 0.01wt%, 0.015wt%, 0.02wt%, 0.025wt%, 0.03wt%, 0.035wt%, 0.04wt%, 0.045wt% or 0.050wt%. Within this range, it can be ensured that the fluorine-containing monomer has a high conversion rate, the fluorine-containing monomer is fully reacted, and the residual fluorine-containing monomer is prevented from affecting the battery performance.
[0078] In a specific embodiment, the precursor solution includes, by weight percentage, 8-17wt% of fluorinated monomer, 0.8-1.5wt% of cross-linking agent, 0.01-0.05wt% of initiator, and the balance is electrolyte. At this time, the fluorinated monomer, initiator, cross-linking agent and electrolyte can better cooperate and synergize to form a more stable and dense SEI film, thereby further reducing the interface impedance, and at the same time, better inhibiting the occurrence of side reactions between the electrolyte and the active material, further reducing the loss of irreversible capacity, thereby comprehensively improving the rate performance and high temperature storage performance of the gel battery.
[0079] The gel battery of the present invention is described in detail below through specific embodiments.
[0080] Example 1
[0081] 1) trifluoroethyl methacrylate, pentaerythritol tetraacrylate, electrolyte, and initiator azobisisobutyronitrile are mixed in a mass ratio of 9:1:89.975:0.025 to obtain a uniform precursor solution, wherein the electrolyte comprises lithium hexafluorophosphate (LiPF6), ethylene carbonate (EC), ethyl methyl carbonate (EMC), propylene carbonate (PC), fluoroethylene carbonate (FEC), and diethyl carbonate (DEC) in a mass ratio of 12.5:7.75:38.75:7.75:10:23.25;
[0082] 2) Inject 4g of the precursor solution into a baked lithium-ion battery (capacity of about 1Ah), where the negative electrode active material is silicon carbon (Tianmu Pioneer 550) and the positive electrode active material is ternary nickel-cobalt-manganese LiNi 0.8 Mn 0.1 Co 0.1 O2 (NMC811, Rongbai S85E), the diaphragm is a PE ceramic diaphragm; after the liquid is filled and sealed, the first battery is obtained after standing at room temperature 25°C for 24 hours;
[0083] 3) The first battery was cycled twice according to the following charge and discharge mechanism and activated to obtain a second battery, wherein the charge and discharge mechanism is as follows: using a battery clamp, under a pressure of 0.3 MPa, at 25°C, charging at a constant current and constant voltage of 0.1C to a battery working cut-off voltage of 4.25V, a cut-off current of 0.05C, and resting for 5 minutes, and then discharging at a constant current of 0.1C to a battery working cut-off voltage of 2.75V, and resting for 5 minutes;
[0084] 4) The second battery was reacted at a pressure of 0.3 MPa and a temperature of 60° C. for 24 h. After the reaction was completed, it was allowed to stand at room temperature for 24 h. The battery cell was then vented. The secondary venting time was 5 s and the venting vacuum was 90-95 Pa to complete the battery packaging. Finally, the battery was divided into different capacities, and the currents of the divided capacities were 0.1C, 0.3C, 0.5C and 1C, respectively, to obtain the gel battery of this embodiment.
[0085] Example 2
[0086] The preparation method of the gel battery in this embodiment is basically the same as that in Embodiment 1, except that in step 1), the mass ratio of trifluoroethyl methacrylate, pentaerythritol tetraacrylate, electrolyte, and initiator is adjusted to 14:1:84.975:0.027.
[0087] Example 3
[0088] The preparation method of the gel battery in this embodiment is basically the same as that in Embodiment 1, except that in step 3), the pressure is adjusted to 0.1 MPa.
[0089] Example 4
[0090] The preparation method of the gel battery in this embodiment is basically the same as that in Embodiment 1, except that in step 3), the pressure is adjusted to 1 MPa.
[0091] Example 5
[0092] The preparation method of the gel battery in this embodiment is basically the same as that in Embodiment 1, except that in step 4), the pressure is adjusted to 0.1 MPa.
[0093] Example 6
[0094] The preparation method of the gel battery in this embodiment is basically the same as that in Embodiment 1, except that in step 4), the pressure is adjusted to 0.5 MPa.
[0095] Example 7
[0096] The preparation method of the gel battery in this embodiment is basically the same as that in Embodiment 1, except that in step 4), the reaction time is adjusted to 28 hours.
[0097] Example 8
[0098] The preparation method of the gel battery in this embodiment is basically the same as that in Embodiment 1, except that in step 4), the reaction time is adjusted to 32 hours.
[0099] Example 9
[0100] The preparation method of the gel battery in this embodiment is basically the same as that in Embodiment 1, except that in step 1), trifluoroethyl methacrylate is replaced by 1,1,1,3,3,3-hexafluoroisopropyl methacrylate.
[0101] Example 10
[0102] The preparation method of the gel battery in this embodiment is basically the same as that in Embodiment 1, except that in step 1), trifluoroethyl methacrylate is replaced by hexafluorobutyl methacrylate.
[0103] Embodiment 11
[0104] The preparation method of the gel battery in this embodiment is basically the same as that in Embodiment 1, except that in step 1), trifluoroethyl methacrylate is replaced by octafluoropentyl methacrylate.
[0105] Example 12
[0106] The preparation method of the gel battery in this embodiment is basically the same as that in Embodiment 1, except that, in step 1), the mass percentage of trifluoroethyl methacrylate in the precursor solution is adjusted to 6.5wt%, and accordingly, the mass ratio of trifluoroethyl methacrylate, pentaerythritol tetraacrylate, electrolyte, and initiator azobisisobutyronitrile is 6.5:1:92.475:0.025.
[0107] Example 13
[0108] The preparation method of the gel battery in this embodiment is basically the same as that in Embodiment 1, except that, in step 1), the mass percentage of trifluoroethyl methacrylate in the precursor solution is adjusted to 19wt%, and accordingly, the mass ratio of trifluoroethyl methacrylate, pentaerythritol tetraacrylate, electrolyte, and initiator azobisisobutyronitrile is 19:1:79.975:0.025.
[0109] Embodiment 14
[0110] The preparation method of the gel battery in this embodiment is basically the same as that in Embodiment 1, except that, in step 1), the mass percentage of trifluoroethyl methacrylate in the precursor solution is adjusted to 11.5wt%, and accordingly, the mass ratio of trifluoroethyl methacrylate, pentaerythritol tetraacrylate, electrolyte, and initiator azobisisobutyronitrile is 11.5:1:87.475:0.025.
[0111] Embodiment 15
[0112] The preparation method of the gel battery in this embodiment is basically the same as that in Embodiment 1, except that in step 1), pentaerythritol tetraacrylate is replaced by trimethylolpropane triacrylate.
[0113] Example 16
[0114] The preparation method of the gel battery in this embodiment is basically the same as that in Embodiment 1, except that in step 1), pentaerythritol tetraacrylate is replaced by trimethylolpropane trimethacrylate.
[0115] Embodiment 17
[0116] The preparation method of the gel battery in this embodiment is basically the same as that in Embodiment 1, except that in step 1), azobisisobutyronitrile is replaced by azobisisoheptanenitrile.
[0117] Embodiment 18
[0118] The preparation method of the gel battery in this embodiment is basically the same as that in Embodiment 1, except that, in step 1), the mass percentage of pentaerythritol tetraacrylate in the precursor solution is adjusted to 0.8wt%, and accordingly, the mass ratio of trifluoroethyl methacrylate, pentaerythritol tetraacrylate, electrolyte, and initiator azobisisobutyronitrile is 9:0.8:90.175:0.027.
[0119] Embodiment 19
[0120] The preparation method of the gel battery in this embodiment is basically the same as that in Embodiment 1, except that, in step 1), the mass percentage of pentaerythritol tetraacrylate in the precursor solution is adjusted to 2wt%, and accordingly, the mass ratio of trifluoroethyl methacrylate, pentaerythritol tetraacrylate, electrolyte, and initiator azobisisobutyronitrile is 9:2:88.975:0.025.
[0121] Embodiment 20
[0122] The preparation method of the gel battery in this embodiment is basically the same as that in Embodiment 1, except that, in step 1), the mass percentage of azobisisobutyronitrile in the precursor solution is adjusted to 0.01wt%, and accordingly, the mass ratio of trifluoroethyl methacrylate, pentaerythritol tetraacrylate, electrolyte, and initiator azobisisobutyronitrile is 9:1:89.99:0.01.
[0123] Embodiment 21
[0124] The preparation method of the gel battery in this embodiment is basically the same as that in Embodiment 1, except that, in step 1), the mass percentage of azobisisobutyronitrile in the precursor solution is adjusted to 0.5wt%, and accordingly, the mass ratio of trifluoroethyl methacrylate, pentaerythritol tetraacrylate, electrolyte, and initiator azobisisobutyronitrile is 9:1:89.95:0.5.
[0125] Embodiment 22
[0126] The preparation method of the gel battery in this embodiment is basically the same as that in Example 1, except that, in step 1), the content of fluoroethylene carbonate (FEC) in the electrolyte is adjusted to 5wt%, that is, the mass ratio of lithium hexafluorophosphate (LiPF6), ethylene carbonate (EC), ethyl methyl carbonate (EMC), propylene carbonate (PC), fluoroethylene carbonate (FEC) and diethyl carbonate (DEC) in the electrolyte is 12.5:9:40:9:5:24.5.
[0127] Embodiment 23
[0128] The preparation method of the gel battery in this embodiment is basically the same as that in Example 1, except that, in step 1), the content of fluoroethylene carbonate (FEC) in the electrolyte is adjusted to 12wt%, that is, the mass ratio of lithium hexafluorophosphate (LiPF6), ethylene carbonate (EC), ethyl methyl carbonate (EMC), propylene carbonate (PC), fluoroethylene carbonate (FEC) and diethyl carbonate (DEC) in the electrolyte is 12.5:7.25:38.25:7.25:12:22.75.
[0129] Embodiment 24
[0130] The preparation method of the gel battery in this embodiment is basically the same as that in Embodiment 1, except that, in step 1), the mass percentage of trifluoroethyl methacrylate in the precursor solution is adjusted to 20wt%, and accordingly, the mass ratio of trifluoroethyl methacrylate, pentaerythritol tetraacrylate, electrolyte, and initiator azobisisobutyronitrile is 20:1:78.975:0.025.
[0131] Embodiment 25
[0132] The preparation method of the gel battery in this embodiment is basically the same as that in Embodiment 1, except that, in step 1), the mass percentage of pentaerythritol tetraacrylate in the precursor solution is adjusted to 2.5wt%, and accordingly, the mass ratio of trifluoroethyl methacrylate, pentaerythritol tetraacrylate, electrolyte, and initiator azobisisobutyronitrile is 9:2.5:88.475:0.025.
[0133] Embodiment 26
[0134] The preparation method of the gel battery in this embodiment is basically the same as that in Embodiment 1, except that, in step 1), the mass percentage of azobisisobutyronitrile in the precursor solution is adjusted to 0.1wt%, and accordingly, the mass ratio of trifluoroethyl methacrylate, pentaerythritol tetraacrylate, electrolyte, and initiator azobisisobutyronitrile is 9:1:89.9:0.1.
[0135] Embodiment 27
[0136] The preparation method of the gel battery in this embodiment is basically the same as that in Embodiment 1, except that in step 3), the charge and discharge current is adjusted to 0.08C.
[0137] Embodiment 28
[0138] The preparation method of the gel battery in this embodiment is basically the same as that in Embodiment 1, except that in step 3), the charge and discharge current is adjusted to 0.12C.
[0139] Comparative Example 1
[0140] The preparation method of the lithium ion battery in this comparative example is basically the same as that in Example 1, except that, in step 2), after the liquid is injected and sealed, the battery is left to stand at 25° C. for 3 hours to obtain the first battery;
[0141] In step 3), the first battery is reacted at a pressure of 0.3MPa and a temperature of 60°C for 24h. After the reaction is completed, it is allowed to stand at room temperature for 24h, and then subjected to formation treatment at a pressure of 0.3MPa, a temperature of 45°C, a formation current of 0.1C, and a formation time of 390min; the battery after formation is aged at an aging temperature of 45°C, a pressure of 3MPa, and a time of 16h; then the battery cell is exhausted, the secondary exhaust time is 5s, the exhaust vacuum is 90-95Pa, and the battery packaging is completed; finally, the battery is divided into different capacities, and the divided currents are 0.1C, 0.3C, 0.5C and 1C, respectively, to obtain the semi-solid-state battery of this comparative example.
[0142] Comparative Example 2
[0143] The preparation method of the lithium ion battery in this comparative example is basically the same as that in Example 2, except that, in step 2), after the liquid is injected and sealed, the battery is left to stand at 25° C. for 3 hours to obtain the first battery;
[0144] In step 3), the first battery is reacted at a pressure of 3MPa and a temperature of 60°C for 24h. After the reaction is completed, it is allowed to stand at room temperature for 24h, and then subjected to formation treatment at a pressure of 3MPa, a temperature of 45°C, a formation current of 0.1C, and a formation time of 390min; the battery after formation is aged at an aging temperature of 45°C, a pressure of 3MPa, and a time of 16h; then the battery cell is exhausted, the secondary exhaust time is 5s, the exhaust vacuum is 90-95Pa, and the battery packaging is completed; finally, the battery is divided into different capacities, and the currents of the divided capacities are 0.1C, 0.3C, 0.5C and 1C, respectively, to obtain the semi-solid-state battery of this comparative example.
[0145] Comparative Example 3
[0146] The preparation method of the gel battery in this comparative example is basically the same as that in Example 1, except that in step 3), the pressure is adjusted to 2 MPa.
[0147] Comparative Example 4
[0148] The preparation method of the gel battery in this comparative example is basically the same as that in Example 1, except that in step 4), the pressure is adjusted to 0 MPa and the temperature is adjusted to 80°C.
[0149] Comparative Example 5
[0150] The preparation method of the gel battery in this comparative example is basically the same as that in Example 1, except that in step 4), the reaction time is adjusted to 48°C.
[0151] Comparative Example 6
[0152] The preparation method of the gel battery in this comparative example is basically the same as that in Example 1, except that in step 1), the reaction monomer is replaced by ethyl acrylate instead of trifluoroethyl methacrylate.
[0153] Comparative Example 7
[0154] The preparation method of the gel battery in this embodiment is basically the same as that in Embodiment 1, except that in step 3), the charge and discharge current is adjusted to 0.2C.
[0155] Test example
[0156] 1. Testing the high temperature storage performance and rate performance of the lithium ion batteries in the embodiments and comparative examples comprises the following steps:
[0157] 1) High-temperature storage capacity remaining rate and capacity recovery rate
[0158] The lithium-ion battery is charged to 4.25V at a current density of 1C to obtain a fully charged battery, and the thickness of the fully charged battery is measured to obtain an initial thickness T0; the internal resistance of the battery is tested with a resistance meter to obtain an initial internal resistance R0; at room temperature 25°C, the fully charged battery is discharged for 30min to 2.75V, and then discharged for 10s to 2.75V after being left for 1h to obtain an initial DC resistance DCR0; the discharge capacity obtained by 1C discharge during capacity division is defined as the initial discharge capacity C0;
[0159] The fully charged battery was placed in a 60°C constant temperature oven for storage for 14 days. After the storage, the thickness of the battery after storage was measured to obtain the battery thickness T1. The internal resistance of the battery after storage was tested using a resistance meter to obtain the battery internal resistance R1. At room temperature of 25°C, the stored battery was discharged for 30 minutes to 2.75V, left for 1 hour, and then discharged for 10 seconds to 2.75V, and the DC resistance DCR1 of the stored battery was obtained by testing.
[0160] At room temperature 25°C, the stored battery was discharged at 1C to 2.75V to obtain a discharge capacity C1; then, the battery was charged and discharged for 3 cycles at 1C between 2.75V and 4.25V to obtain a discharge capacity C2 after the cycle;
[0161] Then the high temperature storage capacity retention rate, high temperature storage capacity recovery rate, high temperature storage internal resistance change rate, high temperature storage thickness expansion rate, and DC resistance change rate are calculated by formula 1, formula 2, formula 3, formula 4, and formula 5, respectively.
[0162] High temperature storage capacity retention rate (%) = (C1 / C0) × 100% Formula 1
[0163] High temperature storage capacity recovery rate (%) = (C2 / C1) × 100% Formula 2
[0164] High temperature storage internal resistance change rate (%) = (R1 / R0) × 100% Formula 3
[0165] High temperature storage thickness expansion rate (%) = (T1 / T0) × 100% Formula 4
[0166] High temperature storage DC resistance change rate (%) = (DCR1 / DCR0) × 100% Formula 5.
[0167] The test and calculation results are shown in Table 1.
[0168] 2) Rate performance
[0169] The lithium ion batteries in the above embodiments and comparative examples were tested for rate performance using a high-precision battery performance test system. The specific method was as follows: 1C, 2C, 3C and 1C were cycled 10 times at 2.75-4.25V, and the average discharge capacity during the initial 10 cycles at 1C was recorded as C3, and the average discharge capacity during the final 10 cycles at 1C was recorded as C4. Then, the 1C capacity recovery rate (%) = (C4 / C3) × 100%. On this basis, 1C was cycled for 200 cycles at 2.75-4.25V. The test results are shown in Tables 2 and 3. Figure 1 , Figure 2 .
[0170] Figure 2 The discharge capacity variation diagram of the gel battery in Example 1 and Comparative Example 1 at different rates is shown in FIG. Figure 3 The following is a graph showing the discharge capacity variation of the gel battery in Example 2 and Comparative Example 2 at different rates. Figure 2 and Figure 3 It can be seen that Example 1 has higher rate discharge performance than Comparative Example 2, and Example 2 has higher rate discharge performance than Comparative Example 2.
[0171] Table 1
[0172]
[0173]
[0174] Table 2
[0175]
[0176]
[0177] From Table 1 and Table 2, we can see that:
[0178] Compared with Comparative Examples 1 to 7, Examples 1 to 28 have higher high-temperature storage performance and rate performance, wherein the capacity retention rate of the lithium-ion battery in Example 2 under high-temperature storage is as high as 70.5%, the capacity recovery rate is as high as 74.3%, the internal resistance change rate is as low as 45.7%, and the resistance change rate is as low as 40.3%. Accordingly, the high-temperature storage thickness expansion rate is 10.3%, and the 1C capacity recovery rate is as high as 98.6%. Although the expansion rate is relatively high, it is still within an acceptable range, and the comprehensive performance is obviously higher than the lithium-ion batteries in Comparative Examples 1 to 7. Therefore, the gel battery in the present invention has higher rate performance and high-temperature storage performance.
[0179] 2. AC impedance test was performed on the gel batteries in the above-mentioned embodiments 1 and 2, comparative examples 1 and 2, and the gel batteries in the above-mentioned embodiments 1 and 2, comparative examples 1 and 2 after being stored according to the above-mentioned high temperature storage method. The test conditions are: AC impedance test was performed using an electrochemical workstation at a frequency of 0.04 Hz-10 5 Hz, AC amplitude is 10mV, and the AC impedance spectrum (EIS) is obtained. The test results are shown in Figure 4-Figure 7 .
[0180] Figure 4 This is the EIS test diagram of the gel battery in Example 1 before and after high temperature storage. Figure 5 This is the EIS test diagram of the gel battery in Example 2 before and after high temperature storage. Figure 6 This is the EIS test diagram of the gel battery in Comparative Example 1 before and after high temperature storage. Figure 7 This is the EIS test diagram of the gel battery in Comparative Example 2 before and after high temperature storage. In the EIS test, the larger the radius of the first arc in the curve, the more intense the interface reaction; Figure 4-Figure 5 and Figure 6-Figure 7 It can be seen that the radius of the first arc in the EIS test curves of Comparative Examples 1 and 2 is significantly larger than that of Example 1 and Example 2; thus, it can be seen that the gel battery prepared by the preparation method of the present invention can effectively reduce the SEI film impedance, and the polymer contains fluorine, which helps to stabilize the SEI film and further reduce the interface impedance and battery internal resistance.
[0181] 3. The cross-section of the negative electrode active material in the gel battery of Example 2 and Comparative Example 2 was subjected to SEM test. The test results are shown in Figure 8-Figure 11 .
[0182] Figure 8 is a cross-sectional SEM image of the negative electrode active material in the gel battery in Example 2 at 6.00K, Fig. 9 is a cross-sectional SEM image of the negative electrode active material in the gel battery in Example 2 at 10.0k, Fig.10is a cross-sectional SEM image of the negative electrode active material in the gel battery in Comparative Example 2 at 6.00 K, Fig.11 This is a cross-sectional SEM image of the negative electrode active material in the gel battery in Comparative Example 2 at 10.0k. Figure 8-Figure 11 It can be seen that the surface of the negative electrode active material in Example 2 contains a coating layer with a small thickness of about 0.42 μm, and under high rate Fig. 9 It can be seen that the coating layer contains obvious light and dark irregular areas; while the surface of the negative electrode active material in Comparative Example 2 also contains a coating layer, but the thickness is thicker, about 0.58μm, and under high magnification Fig.11 It can be seen that there are almost no obvious light and dark irregular areas in the coating layer, and only a very small part exists; combined with the internal resistance and DC impedance data of the lithium ion batteries in Example 2 and Comparative Example 2 in Table 1 above, it can be inferred that the bright area may be the SEI film, and the dark area may be the polymer. It is precisely because more SEI films are formed on the surface of the negative electrode active material in Example 2, and almost no SEI film is formed in the surface coating layer of the negative electrode active material in Comparative Example 2, that the DC impedance and internal resistance of the battery in Comparative Example 2 are significantly higher than those in Example 2.
[0183] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A gel battery, characterized in that: The gel battery comprises a negative electrode sheet and a gel electrolyte; The gel electrolyte comprises an electrolyte and a gel polymer, and the gel polymer is obtained by polymerizing a raw material system comprising a fluorine-containing monomer; The negative electrode sheet comprises a negative electrode active material, wherein the negative electrode active material comprises a core and a coating layer, wherein the coating layer comprises a first coating layer and a second coating layer, wherein the first coating layer is located on at least a portion of an outer surface of the core, and the second coating layer is located on a surface of the first coating layer away from the core, or the second coating layer is located on a surface of the first coating layer away from the core and on a surface of the core; The core includes a negative electrode material that can be used for active ion embedding and extraction, the first coating layer includes a SEI film, and the second coating layer includes the gel polymer; The coating layer has a thickness of 0.3-0.5 μm.
2. The gel battery according to claim 1, characterized in that: The fluorine-containing monomer includes at least one of trifluoroethyl methacrylate, 1,1,1,3,3,3-hexafluoroisopropyl methacrylate, trifluoroethyl acrylate, hexafluorobutyl acrylate, hexafluorobutyl methacrylate, and octafluoropentyl methacrylate.
3. The gel battery according to claim 1 or 2, characterized in that: The electrolyte includes an additive; The additive includes fluoroethylene carbonate and / or vinylene carbonate.
4. The method for preparing a gel battery according to claim 3, characterized in that: The mass percentage of the additive in the electrolyte is 5-12wt%.
5. A method for preparing a gel battery according to any one of claims 1 to 4, characterized in that: The following steps are involved: 1) injecting a precursor solution including an electrolyte and a fluorine-containing monomer into a battery to obtain a first battery; 2) Cycling the first battery 1-2 times according to the following charge and discharge mechanism to obtain a second battery; The charging and discharging mechanism includes: charging at a constant current and constant voltage of 0.08-0.12C to the battery working cut-off voltage at a pressure of 0.1-1.0MPa and a temperature not higher than 25°C, with a cut-off current of 0.05C, and then discharging at a constant current of 0.08-0.12C to the battery working cut-off voltage and standing still; 3) reacting the second battery at a pressure of 0.1-0.5 MPa and a temperature of 55-70° C. for a reaction time of not less than 24 hours to obtain the gel battery.
6. The method for preparing a gel battery according to claim 5, characterized in that: The mass percentage of the fluorine-containing monomer in the precursor solution is 6.5-19.0 wt %.
7. The method for preparing a gel battery according to claim 5 or 6, characterized in that: The precursor solution also includes a cross-linking agent; The crosslinking agent includes at least one of pentaerythritol tetraacrylate, di(trimethylolpropane) tetraacrylate, trimethylolpropane triacrylate, and trimethylolpropane trimethacrylate; And / or, the precursor solution further comprises an initiator; The initiator includes azobisisobutyronitrile and / or azobisisoheptanenitrile.
8. The method for preparing a gel battery according to claim 7, characterized in that: The mass percentage of the cross-linking agent in the precursor solution is 0.8-2.0 wt %.
9. The method for preparing a gel battery according to claim 7, characterized in that: The mass percentage of the initiator in the precursor solution is 0.01-0.05wt%.
10. The method for preparing a gel battery according to claim 9, characterized in that: The precursor solution comprises, in terms of mass percentage, 8-17 wt % of a fluorine-containing monomer, 0.8-1.5 wt % of a cross-linking agent, 0.01-0.05 wt % of an initiator, and the remainder being an electrolyte.
Citation Information
Patent Citations
Application method of conductive ion gel copolymer in battery cell and battery cell
CN113903976A
Functional quasi-solid polymer electrolyte as well as preparation method and application thereof
CN115986205A
Gel polymer electrolyte, semi-solid lithium ion battery and preparation method of semi-solid lithium ion battery
CN117810529A